A study of digital piracy behavior among undergraduate students in the context of Higher education, Universiti Teknologi Mara / Shamshul Anaz Kassim...[et al.] - Anaz Kassim, Shamshul; Ahmad Fuaad, Rokiah; Mhd Nasir, Nurul Farihin; Ali, Jati Kasuma (Universiti Teknologi MARA, Kedah, 2019)
This paper outlines an empirical study, which seeks to identify digital piracy behavior among undergraduate students, Universiti Teknologi MARA (UiTM). This study was conducted to find out the factors such as moral equity, relativism, attitude, religiosity and social influence and how they affect digital piracy behavior towards UiTM undergraduate students. By investigating these factors, the researcher will be able to know the most critical factor that contributes to the digital piracy behavior. The respondents were undergraduate students with the total of 340 respondents. The technique used was stratified random sampling. All five independent variables were found significant relationship with digital piracy behavior. The most significant and related to the digital piracy behavior were relativism, attitude and religiosity. Moral equity, relativism, attitude, religiosity and social influence were found to have a relationship to digital piracy behavior among undergraduate students.